2021
DOI: 10.3390/ijerph18073652
|View full text |Cite
|
Sign up to set email alerts
|

Co-Use of Alcohol and Cannabis: Longitudinal Associations with Mental Health Outcomes in Young Adulthood

Abstract: Increases in cannabis use among young people has heightened concern about the potential interactive health effects of cannabis with other drugs. We examined the longitudinal association between concurrent and simultaneous (SAM) co-use of alcohol and cannabis in young adulthood on mental health symptoms, substance use behaviors, and substance-related harms two years later. Data were drawn from Time 5 (T5; n = 464; 46% male) and 6 (T6; n = 478; 45% male) of the Victoria Healthy Youth Survey. At T5, 42% of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“… 23 Compared to alcohol-only use, SAM use and SAM use frequency were associated with higher levels of psychosis, oppositional defiant disorder, and conduct disorder in a community sample of young adults. 28 Another paper found that young adults who reported more depressive symptoms across 2 years also reported more frequent SAM use; furthermore, during months with more depressive symptoms, young adults engaged in more SAM use compared to months when they used alcohol only (levels of depressive symptoms did not differ across months with SAM use compared to neither alcohol nor marijuana or concurrent use). 65 Further, SAM use was positively associated with likelihood of alcohol dependence.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“… 23 Compared to alcohol-only use, SAM use and SAM use frequency were associated with higher levels of psychosis, oppositional defiant disorder, and conduct disorder in a community sample of young adults. 28 Another paper found that young adults who reported more depressive symptoms across 2 years also reported more frequent SAM use; furthermore, during months with more depressive symptoms, young adults engaged in more SAM use compared to months when they used alcohol only (levels of depressive symptoms did not differ across months with SAM use compared to neither alcohol nor marijuana or concurrent use). 65 Further, SAM use was positively associated with likelihood of alcohol dependence.…”
Section: Resultsmentioning
confidence: 97%
“…Most papers examining gender and/or sex differences in SAM use, including those using nonrepresentative samples, found that a greater proportion of males than females engaged in SAM use. 15 , 23 28 One paper also found that males consumed greater amounts of alcohol and were high for greater lengths of time on SAM use days than females. 29 Fewer papers examined race/ethnicity differences.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, cross-sectional work consistently shows that even subclinical mental health symptoms (assessed as depressive or anxiety symptoms) can be associated with risky substance use patterns when alcohol and marijuana use behaviors are tested separately (e.g., Acuff et al, 2018; Buckner et al, 2010; Geisner et al, 2018; Villarosa-Hurlocker et al, 2019). Although the Thompson et al (2021) study is an important first step in understanding the relationship between SAM use and mental health symptoms, it did not examine the association of acute (i.e., daily) mental health symptoms and SAM use or the role of other important proximal predictors of substance use that are salient among those with mental health problems (i.e., coping motives).…”
Section: Mental Health Symptomsmentioning
confidence: 99%
“…Although there are high rates of comorbid substance use disorders and mental health disorders in young adults broadly (Arterberry et al, 2020), only one known study has tested associations between SAM use and mental health symptoms specifically. In a longitudinal study of young adults, individuals who endorsed any SAM use (compared to those who only used alcohol) and those who engaged in frequent SAM use experienced lower levels of anxiety symptoms (but not depression) 2 years later (Thompson et al, 2021). Although these findings are somewhat consistent with prior studies examining alcohol and marijuana use behaviors separately (e.g., Cranford et al, 2009), cross-sectional work has found that young adults who reported mental health symptoms were more likely to report alcohol and marijuana co-use (i.e., use of marijuana and use of alcohol within the past month, but not necessarily at the time) than alcohol only use (Cohn et al, 2018).…”
mentioning
confidence: 99%